Al-Qur’an and Economy: The Reflection of Developing the Economic Welfare - Zulfikar, Eko (Khatulistiwa, 2020)
In the world of economy, meeting needs and achieving desires has become a priority in human life. The manifestation of the priorities is basically not solely from the results of his own efforts, but there is the engagement of other people who contribute to the success of his business. With this understanding, the attitude will give rise to not operate assets for his personal interests, but also includes the advantage of the public. This paper will introduce how to advantage in the economy summarized by the Qur’an. By using the thematic method and data analysis in intertextuality, it was concluded that there were at least six advantages in the economy based on Quran perspective which should be obeyed namely; economic activities are not illegal, optimizing natural resources, distributing the results, not abuse one another, there should be balance and simplicity, and consuming something that is lawful and thayyib